Junior female ice hockey players; behavioural strategies in training process - Biserova, G. K.; Gaifullina, N. G. (Theory and Practice of Physical Culture, 2018)
The study was designed to analyze the junior female ice hockey players` behavioural strategies in the training process. Due understanding and control of such strategies is indispensable for success of training systems in the individual athletic resource mobilization and development aspects. At least five basic behavioural strategies are analyzed in modern psychology which are the following: competition, collaboration, compromise, avoidance and accommodation. We believe that competition and collaboration behavioural patterns development initiatives should be in high priority for competitive success in junior ice hockey. The collaboration behavioural strategies are considered the most beneficial for competitive teamwork, while a high competitive spirit is paramount for victories in team sports. Having analyzed the behavioural patterns of the 7-9 year-old boys and girls, we found some minor differences in their behavioural strategies. Objective of the study was to rate and analyze variations in the junior female ice hockey players` behavioural strategies in the training process. Subject to the study were junior (7-9 year-old) female (n=20) and male (n=25) ice hockey players. The hierarchy of the junior players` behavioural strategies was found largely gender-unspecific in the following categories: 1 - competition; 2 - collaboration; 3 - compromise; 4 - avoidance; and 5 - accommodation; with the competition and collaboration strategies ranked dominant. Statistically significant minor differences in the behavioural strategies were found only in the compromise and accommodation strategies more developed in girls and correlated with a variety of their natural personality qualities including patience, tranquility, dependence, prudence, care and gentleness. The study confirmed the prior assumptions on the behavioural strategy variations in the junior female athletes.